Patient-reported quality indicators for osteoarthritis: a patient and public generated self-report measure for primary care. Issue 1 (December 2016) - Blackburn, Steven; Higginbottom, Adele; Taylor, Robert; Bird, Jo; Østerås, Nina; Hagen, Kåre; Edwards, John; Jordan, Kelvin; Jinks, Clare; Dziedzic, Krysia
Plain English summary People with osteoarthritis desire high quality care, support and information. However, the quality of care for people with OA in general practice is not routinely collected. Quality Indicators can be used to benefit patients by measuring whether minimum standards of quality care are being met from a patient perspective. The aim of this study was to describe how a Research User Group (RUG) worked alongside researchers to co-produce a set of self-reported quality indicators for people with osteoarthritis when visiting their general practitioner or practice nurse (primary care). These were required in the MOSAICS study, which developed and evaluated a new model of supported self-management of OA to implement the NICE quality standards for OA. This article describes the public involvement in the MOSAICS study. This was 1) the co-development by RUG members and researchers of an Osteoarthritis Quality Indicators United Kingdom (OA QI (UK)) questionnaire for use in primary care, and 2) the comparison of the OA QI (UK) with a similar questionnaire developed in Norway. This study shows how important and effective a research user group can be in working with researchers in developing quality care indicators for osteoarthritis for use in a research study and, potentially, routine use in primary care. The questionnaire is intended to benefit patients by enabling the assessment of the quality of primary care for osteoarthritis from a patient's perspective. The OA QI (UK) has been used to examine differences in the quality of osteoarthritis care in four European countries. Abstract Background People with osteoarthritis (OA) desire high quality care, support and information about OA. However, the quality of care for people with OA in general practice is not routinely collected. Quality Indicators (QI) can be used to benefit patients by measuring whether minimum standards of quality care (e.g. NICE quality standards) are being met from a patient perspective. A Research User Group (RUG) worked with researchers to co-produce a set of self-report, patient-generated QIs for OA. The QIs were intended for use in the MOSAICS study, which developed and evaluated a new model of supported self-management of OA to implement the NICE guidelines. We report on 1) the co-development of the OA QI (UK) questionnaire for primary care; and 2) the comparison of the content of the OA QI (UK) questionnaire with a parallel questionnaire developed in Norway for the Musculoskeletal Pain in Ullensaker (MUST) study. Methods Researchers were invited to OA RUG meetings. Firstly, RUG members were asked to consider factors important to patients consulting their general practitioner (GP) for OA and then each person rated their five most important. RUG members then discussed these in relation to a systematic review of OA QIs in order to form a list of OA QIs from a patient perspective. RUG members suggested wording and response options for a draft OA QI (UK) questionnaire to assess the QIs. Finally RUG members commented on draft and final versions of the questionnaire and how it compared with a translated Norwegian OA-QI questionnaire. Results RUG members (5 males, 5 females; aged 52–80 years) attended up to four meetings. RUG members ranked 20 factors considered most important to patients consulting their GP for joint pain. Following discussion, a list of eleven patient-reported QIs for OA consultations were formed. RUG members then suggested the wording and response options of 16 draft items – four QIs were split into two or more questionnaire items to avoid multiple dimensions of care quality within a single item. On comparison of this to the Norwegian OA-QI questionnaire, RUG members commented that both questionnaires contained seven similar QIs. The RUG members and researchers agreed to adopt the Norwegian OA-QI wording for four of these items. RUG members also recommended adopting an additional seven items from the Norwegian OA-QI with some minor word changes to improve their suitability for patients in the UK. One other item from the draft OA QI (UK) questionnaire was retained and eight items were excluded, resulting in a 15-item final version. Conclusions This study describes the development of patient-reported quality indicators for OA primary care derived by members of a RUG group, working in partnership with the research team throughout the study. The OA QI (UK) supports the NICE quality standards for OA and they have been successfully used to assess the quality of OA consultations in primary care in the MOSAICS study. The OA QI (UK) has the potential for routine use in primary care to assess the quality of OA care provided to patients. Ongoing research using both the UK and Norwegian OA-QI questionnaires is assessing the self-reported quality of OA care in different European populations.